SWOT Analysis in Developing Dairy Farming Agribusiness Strategy (Case Study of "KPSBU" Lembang West Bandung Regency) - Abdullah, Edi; Ambar, Abdul Azis; Toaha, Sahabuddin (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Livestock has a strategic role in supporting food security and economic development in Indonesia. West Bandung Regency is one of the interesting locations to study in the context of developing an agribusiness system. Despite its great potential, there are challenges in livestock development such as limited market access, the lack of distribution networks, lack of knowledge about market needs and preferences, and obstacles in complying with applicable quality standards and regulations, then the lack of supporting infrastructure and climate change. This study aims to determine the sub-district area that can be used as the basis for the development strategy of the dairy farming agribusiness system with specific contributions to the development of productivity, product diversification, farmer skills and the development of supporting infrastructure. The forms of research used are quantitative and qualitative that complement each other in a mixed approach to collect extensive data on the results of the research, conduct interviews to explore specific findings and validate the findings in the context of a deeper understanding of the data found. The sample used was 10 farmers with a purposive sampling technique. Data was collected from May to July 2024. The data collected is analyzed and if necessary validated with participants to ensure its accuracy and relevance. Data collection techniques are carried out using LQ analysis techniques, EFE and IFE analysis and SWOT analysis to produce concrete strategic solutions. The instruments in this study use an interview, observation and questionnaire system to facilitate data processing. The results showed that the total score of the weight of internal and external factors was located in the position of quadrant I (2,464 ; 2,696). If the position of the quadrant is in quadrant 1, the strategy is an aggressive growth strategy. This is very advantageous because it has strengths and opportunities. Keywords: Agribusiness, IE Matrix, LQ, SWOT